Comparative genomic study of the Penicillium genus elucidates a diverse pangenome and 15 lateral gene transfer events - Celine Petersen; Trine Sørensen; Mikkel R. Nielsen; Teis E. Sondergaard; Jens L. Sørensen; David A. Fitzpatrick; Jens C. Frisvad; Kåre L. Nielsen (IMA Fungus)
Abstract The Penicillia are known to produce a wide range natural products—some with devastating outcome for the agricultural industry and others with unexploited potential in different applications. However, a large-scale overview of the biosynthetic potential of different species has been lacking. In this study, we sequenced 93 Penicillium isolates and, together with eleven published genomes that hold similar assembly characteristics, we established a species phylogeny as well as defining a Penicillium pangenome. A total of 5612 genes were shared between ≥ 98 isolates corresponding to approximately half of the average number of genes a Penicillium genome holds. We further identified 15 lateral gene transfer events that have occurred in this collection of Penicillium isolates, which might have played an important role, such as niche adaption, in the evolution of these fungi. The comprehensive characterization of the genomic diversity in the Penicillium genus supersedes single-reference genomes, which do not necessarily capture the entire genetic variation.